2007
DOI: 10.1152/ajpheart.01221.2006
|View full text |Cite
|
Sign up to set email alerts
|

PTEN reduces cuff-induced neointima formation and proinflammatory cytokines

Abstract: reduces cuff-induced neointima formation and proinflammatory cytokines. Am J Physiol Heart Circ Physiol 292: H2824 -H2831, 2007. First published February 2, 2007; doi:10.1152/ajpheart.01221.2006.-An inflammatory response followed by vascular injury plays an important role in neointima formation and development of atherosclerotic lesions, which are in part mediated by proinflammatory cytokines. Using a cuff injury model, we examined the effects of adenovirusmediated overexpression of phosphatase and tensin homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…[57][58][59][60][61] It was also reported that disruption of PTEN in macrophages significantly increases their phagocytic capability, 22 and that overexpression of PTEN inhibits macrophage invasion and proinflammatory cytokine expression. 62 In our myeloid-specific PTEN KO mice, PTEN expression was also ablated in monocytes, macrophages, and some dendritic cells, which also play critical roles in host defense in bacterial pneumonia. Although the competitive adoptive transfer and in vitro bacteria killing/phagocytosis assays definitively demonstrated that PTEN disruption in neutrophils is at least partially responsible for the enhanced bacteria clearance capability in KO mice, the involvement of other cell types cannot be ruled out.…”
Section: Discussionmentioning
confidence: 72%
“…[57][58][59][60][61] It was also reported that disruption of PTEN in macrophages significantly increases their phagocytic capability, 22 and that overexpression of PTEN inhibits macrophage invasion and proinflammatory cytokine expression. 62 In our myeloid-specific PTEN KO mice, PTEN expression was also ablated in monocytes, macrophages, and some dendritic cells, which also play critical roles in host defense in bacterial pneumonia. Although the competitive adoptive transfer and in vitro bacteria killing/phagocytosis assays definitively demonstrated that PTEN disruption in neutrophils is at least partially responsible for the enhanced bacteria clearance capability in KO mice, the involvement of other cell types cannot be ruled out.…”
Section: Discussionmentioning
confidence: 72%
“…In the current study, we demonstrated that AGEs can strongly enhance miR-214 expression in monocytes, which, in turn, impedes monocyte apoptosis via targeting of the proapoptotic molecule PTEN. As an inhibitor of Akt activation, PTEN was demonstrated to be involved in leukocyte inflammatory responses (52,58,59). Downregulation of PTEN would result in increased Akt activity (Fig.…”
Section: Role Of Mir-214-mediated Targeting Of Pten In Modulating Monmentioning
confidence: 99%
“…The phosphatase domain specifically dephosphorylates the D3 inositol head group of phosphoinositol 3,4,5-triphosphate (PIP 3 ) leading to generation of phosphoinositol 4,5-bisphosphate (PIP 2 ) (1, 2). Thus, through this domain PTEN negatively regulates PI3K-Akt-dependent signaling and thereby controls diverse cellular responses such as neointima formation, neutrophil migration and chemotaxis, angiogenesis, and tumor formation (3)(4)(5)(6)(7)(8)(9). PIP 2 is also the key source for generating cellular diacylglycerol (DAG) and inositol triphosphate, both of which increase intracellular Ca 2ϩ (10).…”
mentioning
confidence: 99%